Engaging and empowering open and distance learning learners: Open University Malaysia experience in leveraging H5P - Bakar, Shawira Abu; Yasin, Nooni Ezdiani; Ahmad Zabidi, Nazrai (Intelektual Pustaka Media Utama, 2026)
The COVID-19 pandemic disrupted the world in unimaginable ways. The repercussions of the pandemic continue until today and one of the most impacted sectors was education. Learning institutions were required to be more creative as face-to-face (F2F) learning could not be held. Hence, Open University Malaysia (OUM) has produced digital learning materials using hypertext markup language (HTML), HTML5 package (H5P) as a technology tool. This concept research paper is a continuation from a research article by OUM entitled measuring the impact of COVID-19 pandemic for continuous development of learning materials. The objectives of this paper are to investigate the impact of adding interactivity to learning materials specifically in H5P format and to identify how impactful the integration of H5P learning materials in the open and distance learning (ODL) environment is. This qualitative study used a mixed method approach involving semi-structured interview and purposive sampling. The findings show approximately 82% of participants were motivated to complete all H5P activities, although about 63% felt that these activities were time-consuming. The interactive components of H5P successfully engage learners in assessment tasks, in the long run, it might lead to boredom due to the perceived time demands associated with these activities.